Penggunaan Media Interaktif Berbasis Video Animasi Dalam Peningkatan Bahasa Ekspresif Pada Siswa Autis di SKH Bougenville Kota Tangerang Selatan - Lutfianti, Zerlinda; Asmiati, Neti; Pratama, Toni Yudha (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The purpose of this study is to provide improvements in expressive language through the use of interactive media with the help of animated videos for autistic students at SKh Bougenville, South Tangerang City. The type of research applied is experimental research with the form of Single Subject Research with an A1-B-A2 design which is included in quantitative research. The problem in this study is the low expressive language ability of autistic individuals. One of the causes is the lack of development and variation of learning media that focuses on expressive language. The subjects in this study were autistic individuals in grade 2 of junior high school at SKh Bougenville, South Tangerang City, namely TC. The target behavior (dependent variable) in this study is expressive language ability, while the free variable (independent variable) is interactive media based on animated videos. From the research produced, it is proven that the application of interactive media assisted by animated videos can improve expressive language skills in autistic students at SKh Bougenville. The mean level of the A1 baseline phase at TC was 40%. The mean level obtained in the intervention phase was 89%, while the A2 baseline obtained was 78%. The resulting research shows that the intervention phase shows a higher percentage compared to the baseline A1 phase. The baseline A2 phase also obtained a higher percentage when compared to the baseline A1 phase. Therefore, the conclusion of the research conducted is that the application of interactive media based on animated videos provides an increase in expressive language skills for autistic individuals at SKh Bougenville, South Tangerang City.